Development of Leaf Area Meter Using Open CV for Smartphone Application - Tony K. Hariadi; Zulfan Fadholi; Anna NN Chamim; Nafi A Utama; Indira Prabasari; Slamet Riyadi (Universitas Ahmad Dahlan, 2018)
This study aimed to design an accurate and practical system of leaf area determination using a smartphone. A software application for leaf area computation was developed using Open CV (Open Source Computer Vision) library. Open CV software was tested to estimate the accuracy of leaf area calculation. Leaf area calculations were undertaken using three different image resolutions to compare their accuracy. The results of the software calculations were then compared with the results of the laboratory leaf area meter to identify any errors. The results showed that higher image resolutions improved accuracy by reducing errors. High resolution image gave higher accuracy, however processing speed decreased. Leaf measurement in this project resulted in accuracy range between 92.8% to 99.0%. It was concluded that the Open CV algorithm gave fast and adequate accuracy for leaf area calculation, and that the smartphone mobile application system was practical for field use.